Knowledge, attitude and practices regarding emergency contraception among married women in Ludhiana, Punjab, India - Saini, Shipra; Kamra, Deepshikha; Singh, Shavinder (International Journal Of Community Medicine And Public Health, 2018)
Background: An unwanted and unintended pregnancy is a major concern in a women’s life as it has its adverse social and health outcomes. Emergency contraception (EC) is safe and effective method that gives women a second chance to prevent unwanted pregnancy after unprotected intercourse. Methods: This is a community based cross sectional study done in field practice area under the department of Community Medicine, Christian Medical College, Ludhiana, Punjab. A total of 400 respondents were selected by stratified random sampling from the list of eligible couples residing in the area. The interview was conducted using semi structured questionnaire, after obtaining their informed consent. Results: The mean age of respondents was 31.44±5.67 years. 68.7% of respondents were using some kind of contraception. Majority (68%) of respondents had heard of emergency contraception and for majority (81.3%) source of information about EC was Media (TV). Out of 272 respondents who had heard of emergency contraception 146 (54.1%) had negative attitude towards emergency contraception and only 30 (8%) had used ECP. Practice of ECP was found to have statistically significant association with employment and history of unwanted pregnancy. Conclusions: EC has a potential to curb the menace of unintended pregnancy thereby decreasing unsafe abortion and maternal mortality. In spite of reasonable awareness of emergency contraception, as found in present study there is wide gap for its usage. Hence behavioural change strategies should be considered to bring attitudinal change on use of emergency contraception.